Leading schools during Covid-19 Results of a qualitative survey at national level - Dello Preite, Francesca (Formazione & insegnamento, 2021)
During the Pandemic caused by Covid-19, the school had to test new didactics, organizational, logistical and communication models aimed to continue to grant all its activities, from the educational training to the administrative services, to face the limits imposed by the lockdown. With reference to this context and in particular paying attention to school management, the article intends to present the planning framework and the results of an exploratory qualitative research conducted with the narrative method that investigated the skills, methods, times, tools and resources to which the principals have applied to direct, coordinate and enhance the human resources of their institutes in order to guarantee to all their pupils the right to a continuous and quality learning, which is an indispensable prerogative for a fair and sustainable human growth.